Antiphospholipid syndrome. Issue 1 (February 2016) - Khamashta, M.; Taraborelli, M.; Sciascia, S.; Tincani, A.
Abstract: Antiphospholipid syndrome (APS) is an autoimmune condition characterized by the occurrence of thrombosis (arterial and/or venous), often multiple, and/or pregnancy morbidity. Thrombosis is one of the major disease mechanisms, mainly caused by activating endothelial cells, monocytes, and platelets. At present, the management of APS patients with a history of thrombosis is based on long-term antithrombotic therapy, due to the high rate of recurrent thrombosis (29% per year without treatment). Obstetrical APS includes heterogeneous pregnancy complications whose pathogenesis has been increasingly elucidated in the past years. This is due to the current management and treatment, as 80% of APS patients achieve a live birth. The standard approach of APS is not supported by extensive evidence and the best options for refractory and incomplete cases need to be clarified. New and promising molecules are under investigation.